2022
DOI: 10.3390/jpm12050727
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Novel Three-Dimensional (3D Fusion) Gross Sampling Protocol for Clear Cell Renal Cell Carcinoma to Overcome Intratumoral Heterogeneity: The Meet-Uro 18 Study

Abstract: We aimed to overcome intratumoral heterogeneity in clear cell renal cell carcinoma (clearRCC). One hundred cases of clearRCC were sampled. First, usual standard sampling was applied (1 block/cm of tumor); second, the whole tumor was sampled, and 0.6 mm cores were taken from each block to construct a tissue microarray; third, the residual tissue, mapped by taking pieces 0.5 × 0.5 cm, reconstructed the entire tumor mass. Precisely, six randomly derived pieces of tissues were placed in each cassette, with the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Both TPS and CPS were studied: usually, a minority (7–15%) of clear cell RCCs harbor diffuse TPS scores (≥50%), while conversely, most of them (85%) show positive PD-L1 expression by using the CPS score (85%). The discrepancy is mainly due to the assessment of TIL and myeloid cells in the CPS, which increases the number of positive cells in the final score [ 68 ]. By focusing on the available clones, Ventana SP142 tends to label much more inflammatory than neoplastic cells, while Ventana SP263 mainly stains tumor cells, such as Dako 22C3.…”
Section: Introductionmentioning
confidence: 99%
“…Both TPS and CPS were studied: usually, a minority (7–15%) of clear cell RCCs harbor diffuse TPS scores (≥50%), while conversely, most of them (85%) show positive PD-L1 expression by using the CPS score (85%). The discrepancy is mainly due to the assessment of TIL and myeloid cells in the CPS, which increases the number of positive cells in the final score [ 68 ]. By focusing on the available clones, Ventana SP142 tends to label much more inflammatory than neoplastic cells, while Ventana SP263 mainly stains tumor cells, such as Dako 22C3.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of the performance in detecting histological features of bad prognosis such as high grade and granular eosinophilic cells [15] with both methods in 38 CCRCC showed that MSTS was significantly more informative than routine sampling [16]. Aside from CCRCC, the usefulness of MSTS in CCRCC has been confirmed by subsequent histological, immunohistochemical, and molecular studies in ovarian carcinoma, mesothelioma, and head and neck squamous cell carcinoma [17][18][19][20]. Lakis et al [17] have analyzed 294 tumor sections from 70 treatment naïve patients who had undergone cytoreductive surgery of ovarian cancer and have observed not only the high histological variability of tumors across different regions, but also the irregular qualitative and quantitative distribution of tumor-associated lymphocyte, information with obvious prognostic and therapeutic implications.…”
Section: Multisite Tumor Sampling (Msts)mentioning
confidence: 98%
“…The authors included in the comparison histological, immunohistochemical, and molecular parameters, and concluded that MSTS was more informative than routine sampling in detecting perineurial permeation, peritumoral vascular/lymphatic growth, necrosis, muscle invasion, PIK3CA mutations (exons 9 and 20), and CDKN2A promoter methylation. Brunelli et al [ 20 ] have recently compared a multi-regional sampling strategy called 3D fusion with routine sampling in 100 CCRCC analyzing the respective performance of both methods in the detection of angiogenic and immune markers. These authors confirm the superiority of 3D fusion sampling and agree that sampling one block/cm of tumor tissue diameter is inadequate to fully characterize ITH in CCRCC.…”
Section: Multisite Tumor Sampling (Msts)mentioning
confidence: 99%
See 2 more Smart Citations